Serglycin determines secretory granule repertoire and regulates natural killer cell and cytotoxic T lymphocyte cytotoxicity. (22nd January 2016) - Sutton, Vivien R.; Brennan, Amelia J.; Ellis, Sarah; Danne, Jill; Thia, Kevin; Jenkins, Misty R.; Voskoboinik, Ilia; Pejler, Gunnar; Johnstone, Ricky W.; Andrews, Daniel M.; Trapani, Joseph A.
Abstract : The anionic proteoglycan serglycin is a major constituent of secretory granules in cytotoxic T lymphocyte (CTL)/natural killer (NK) cells, and is proposed to promote the safe storage of the mostly cationic granule toxins, granzymes and perforin. Despite the extensive defects of mast cell function reported in serglycin gene‐disrupted mice, no comprehensive study of physiologically relevant CTL/NK cell populations has been reported. We show that the cytotoxicity of serglycin‐deficient CTL and NK cells is severely compromised but can be partly compensated in both cell types when they become activated. Reduced intracellular granzyme B levels were noted, particularly in CD27 + CD11b + mature NK cells, whereas serglycin −/− TCR‐transgenic (OTI) CD8 T cells also had reduced perforin stores. Culture supernatants from serglycin −/− OTI T cells and interleukin‐2‐activated NK contained increased granzyme B, linking reduced storage with heightened export. By contrast, granzyme A was not significantly reduced in cells lacking serglycin, indicating differentially regulated trafficking and/or storage for the two granzymes. A quantitative analysis of different granule classes by transmission electronmicroscopy showed a selective loss of dense‐core granules in serglycin −/− CD8 + CTLs, although other granule types were maintained quantitatively. The findings of the present study show that serglycin plays a critical role in the maturation of dense‐core cytotoxic granules in cytotoxic lymphocytes and the trafficking and storage of perforin and granzyme B, whereas granzyme A is unaffected. The skewed retention of cytotoxic effector molecules markedly reduces CTL/NK cell cytotoxicity, although this is partly compensated for as a result of activating the cells by physiological means. Abstract : Normally, Gzms A and B are trafficked to, and stored in Serglycin (SG)‐rich dense‐core secretory granules [1]. In SG−/− CTL/NK cells, dense core granules do not form. Intracellular GzmA levels are maintained by storage in alternative vesicles [2], but GzmB is diverted to a secretory pathway and becomes depleted [3]. SG−/− killer cells also fail to retain and store perforin, and reduced perforin/GzmB causes reduced target cell death.